ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA (STUDI KASUS PADA PERUSAHAAN PT. RAHARDJA EKALANCAR) - Chandra Sagul Haratua; Diandra Rafida Thilal; Wulan Dwi Cahyani (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze human resource development at PT. Rahardja Ekalancar from various aspects. The method used in this study is a qualitative method using a descriptive approach to describe the results of the data. From this study it was found that to develop human resources, PT. Rahardja Ekalancar conducted several methods including training to improve several aspects including productivity, efficiency, damage, accidents, service, morale, career, contextual, leadership, remuneration, and consumers. This is expected to improve and achieve company goals.